Deubiquitinating enzymes regulate Hes1 stability and neuronal differentiation. (23rd April 2015) - Kobayashi, Taeko; Iwamoto, Yumiko; Takashima, Kazuhiro; Isomura, Akihiro; Kosodo, Yoichi; Kawakami, Koichi; Nishioka, Tomoki; Kaibuchi, Kozo; Kageyama, Ryoichiro
<x xml:space="preserve">Abstract</x> Hairy and enhancer of split 1 (Hes1), a basic helix‐loop‐helix transcriptional repressor protein, regulates the maintenance of neural stem/progenitor cells by repressing proneural gene expression via Notch signaling. Previous studies showed that Hes1 expression oscillates in both mouse embryonic stem cells and neural stem cells, and that the oscillation contributes to their potency and differentiation fates. This oscillatory expression depends on the stability of Hes1, which is rapidly degraded by the ubiquitin/proteasome pathway. However, the detailed molecular mechanisms governing Hes1 stability remain unknown. We analyzed Hes1‐interacting deubiquitinases purified from mouse embryonic stem cells using an Hes1‐specific antibody, and identified the ubiquitin‐specific protease 27x (Usp27x) as a new regulator of Hes1. We found that Hes1 was deubiquitinated and stabilized by Usp27x and its homologs ubiquitin‐specific protease 22 (Usp22) and ubiquitin‐specific protease 51 (Usp51). Knockdown of Usp22 shortened the half‐life of Hes1, delayed its oscillation, and enhanced neuronal differentiation in mouse developing brain, whereas mis‐expression of Usp27x reduced neuronal differentiation. These results suggest that these deubiquitinases modulate Hes1 protein dynamics by removing ubiquitin molecules, and thereby regulate neuronal differentiation of stem cells.